Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Siegenthaler, Andy; Buttler, Alexandre; Grosvernier, Philippe; Gobat, Jean-Michel; Nilsson, Mats B.; Mitchell, Edward (My University, 2013)
Eriophorum vaginatum is a characteristic species of northern peatlands and a keystone plant for cutover bog restoration. Understanding the factors affecting E. vaginatum seedling establishment (i.e. growth dynamics and allocation) under global change has practical implications for the management of abandoned mined bogs and restoration of their C-sequestration function. We studied the responses of leaf dynamics, above- and belowground biomass production of establishing seedlings to elevated CO2 and N. We hypothesised that nutrient factors such as limitation shifts or dilutions would modulate growth stimulation. Elevated CO2 did not affect biomass, but increased the number of young leaves in spring (+400 %), and the plant vitality (i.e. number of green leaves/total number of leaves) (+3 %), both of which were negatively correlated to [K+] in surface porewater, suggesting a K-limited production of young leaves. Nutrient ratios in green leaves indicated either N and K co-limitation or K limitation. N addition enhanced the number of tillers (+38 %), green leaves (+18 %), aboveground and belowground biomass (+99, +61 %), leaf mass-to-length ratio (+28 %), and reduced the leaf turnover (-32 %). N addition enhanced N availability and decreased [K+] in spring surface porewater. Increased tiller and leaf production in July were associated with a doubling in [K+] in surface porewater suggesting that under enhanced N production is K driven. Both experiments illustrate the importance of tradeoffs in E. vaginatum growth between: (1) producing tillers and generating new leaves, (2) maintaining adult leaves and initiating new ones, and (3) investing in basal parts (corms) for storage or in root growth for greater K uptake. The K concentration in surface porewater is thus the single most important factor controlling the growth of E. vaginatum seedlings in the regeneration of selected cutover bogs.